Oral telangiectatic granuloma - Eilien Tovio Martínez; Samuel Urbano del Valle; Antonio Díaz Caballero (Editorial Ciencias Médicas, 2018)
Introduction: telangiectatic granuloma is an inflammatory reactive tumor of the oral cavity caused by irritating agents, physical trauma or hormonal factors. It is more frequent in the female sex between the second and sixth decades of life. Objective: describe the clinical-pathological findings of oral telangiectatic granuloma, as well as its possible pathogenesis, differential diagnosis and therapeutic management. Case presentation: data were obtained about the age, sex and clinical diagnosis of a series of five cases of oral telangiectatic granuloma diagnosed at the School of Dentistry of the University of Cartagena in the period 2016-2017. A description is provided of clinical and histological characteristics, etiological factors and symptoms of each case. Histopathology confirmed the diagnosis of telangiectatic granuloma. In all cases treatment was exclusively surgical. Conclusions: it is important for dental professionals to be aware of every single detail concerning telangiectatic granuloma, such as its clinical and histological characteristics and etiological factors, to be able to reach an accurate diagnosis and apply the appropriate therapy.